2013
DOI: 10.1179/1743281213y.0000000138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distribution of biomass fuel in granules on iron ore sintering and NOxemission

Abstract: Pollutant emissions can be reduced by replacing coke breeze with biomass fuels in the sintering process. However, with increasing replacement ratio, yield and tumble index of the sinter decrease due to the increase in sintering vertical speed and the decrease in the combustion efficiency. The distribution of the fuel in the granules affects combustion, and the results of the research indicate that with the biomass fuels wrapped in the granules, the burning speed is reduced and the combustion efficiency improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…Brazil, 16) and our reseach group 17,18) also found the positive influences of charcoal-based biomass fuels replacing coke breeze on SOx and NOx emissions reduction in iron ore sintering process. However, the excessive combustion speed was also the key factor to limit its proper replacement percentage at a lower level.…”
Section: Influence Of Surface Modification On Combustion Characteristmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil, 16) and our reseach group 17,18) also found the positive influences of charcoal-based biomass fuels replacing coke breeze on SOx and NOx emissions reduction in iron ore sintering process. However, the excessive combustion speed was also the key factor to limit its proper replacement percentage at a lower level.…”
Section: Influence Of Surface Modification On Combustion Characteristmentioning
confidence: 99%
“…goethitic, porous hematite ore types and martitic ores) during sintering process had been proposed. 14,18,19) However, little research about surface modification treatment technologies with the purpose of bridging the difference of combustion characteristics between biomass fuels and fossil fuels for iron ore sintering purpose can be found. The surface modification of coke for ironmaking in blast furnace with passivation reagents has been proved to be an effective approach to decrease its reactivity through reducing the surface reaction activity.…”
Section: Influence Of Surface Modification On Combustion Characteristmentioning
confidence: 99%
“…Our 2 Advances in Materials Science and Engineering group also did a lot of work on the influences of biochar replacing coke breeze on sintering process. The research showed that it could reduce emissions of NOx, SOx, and so on when applying the carbonized products of straw, trees, and molded-sawdust [18][19][20][21]. There were lots of differences between biochar and conventional fuels in terms of chemical composition, physical properties, proximate analysis, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Before putting biomass fuels into use on an industrial scale, our group investigated the properties and sintering behaviour of charcoal, charred straw, etc. 14,15) Considerable benefits of these biomass fuels were observed with regard to reduced emissions of CO 2 , SO x and NO x . However, they were found to exhibit greater porosity and specific surface area than coke, especially in the case of straw char, which resulted in degradation of sinter quality if an excessive proportion of coke breeze was replaced.…”
Section: Introductionmentioning
confidence: 99%